STUDENTS’ GEOMETRIC THINKING BASED ON VAN HIELE’S THEORY - Harina Fitriyani; Sri Adi Widodo; Aan Hendroanto (IKIP Siliwangi and I-MES, 2018)
The current study aims to identify the development level of students’ geometric thinking in mathematics education department, Universitas Ahmad Dahlan based on van Hiele’s theory. This is a descriptive qualitative research with the respondents as many as 129 students. In addition to researchers, the instrument used in this study is a test consisting of 25 items multiple choice questions. The data is analyzed by using Milles and Huberman model. The result shows that there were 30,65% of students in pre-visualization level, 21,51% of students in visualizes level, and 29,03% of students in analyze level, 16,67% of students in informal deduction level, 2,15% of students in deduction level, and 0,00% of student in rigor level. Furthermore, findings indicated a transition level among development levels of geometric thinking in pre-analyze, pre-informal deduction, pre-deduction, and pre-rigor that were 20%; 13,44%; 6,45%; 1,08% respectively. The other findings were 40,32% of students were difficult to determine and 4,3% of students cannot be identified.